Economic activities of the Slovak co-operatives in the years 2010 to 2014 - Šúbertová, Elena (Univerzita Pardubice, 2015)
On 9th February 2015, 170 years passed since the first co-operative enterprise had been established in Slovakia. Co-operatives were developing through many stages and their importance at present is different than it used to be in the past. However, the mission of co-operatives has not changed: it is a long- term everyday care of both their members and employees. Currently, over a quarter of million of the Slovak population are either members or workers in one or more co-operatives. The housing and consumers' co-operatives have the most numerous memberships while various small producer co-operatives have the fewest members. For a successful future of Slovak co-operatives, it is inevitable to propose such solutions in the economic and social areas, that will meet needs of their members while taking into consideration customers' requirements. In the current fierce competition, the international collaboration is even more important than it has been before, because local markets are too small for profitable co-operatives. This contribution pays attention to the assessment of economic activities of the Slovak co-operatives in years 2010 to 2014.
Keywords: entrepreneurship; enterprises; employees; members; co-operatives; indicators; SWOT analysis; M13; M21